1997
DOI: 10.1007/s004210050246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intensive swimming training on lung volumes, airway resistances and on the maximal expiratory flow-volume relationship in prepubertal girls

Abstract: The aim of the present study was to analyse the effect of 1 year of intensive swimming training on lung volumes, airway resistance and on the flow-volume relationship in prepubertal girls. Five girls [9.3 (0.5) years old] performing vigorous swimming training for 12 h a week were compared with a control group of 11 girls [9.3 (0.5) years old] who participated in various sport activities for 2 h per week. Static lung volumes, maximal expiratory flows (MEF) at 75, 50 and 25% of vital capacity, 1-s forced expirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
1
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 16 publications
7
58
1
7
Order By: Relevance
“…Adult-smoking sportsmen exhibit some degree of lung-function impairment compared to nonsmoking sportsmen, but still have better lung function than smokers who are not sportsmen [15]. Young swimmers have been found to have better lung function than sedentary youths, as have participants of other sport activities [10,16,17]. An impact of training on lung growth in young swimmers has been suggested [17], but others have found no effect of physical activity on lung growth [18,19].…”
mentioning
confidence: 99%
“…Adult-smoking sportsmen exhibit some degree of lung-function impairment compared to nonsmoking sportsmen, but still have better lung function than smokers who are not sportsmen [15]. Young swimmers have been found to have better lung function than sedentary youths, as have participants of other sport activities [10,16,17]. An impact of training on lung growth in young swimmers has been suggested [17], but others have found no effect of physical activity on lung growth [18,19].…”
mentioning
confidence: 99%
“…This fact was addressed at length in a Thorax editorial 25 While some studies have shown beneficial effects of swimming on pulmonary function test parameters, 11,15 others have failed to show any such effect. 3,10,13,29 However, none of these studies used BHR assessment as a followup tool.…”
Section: Allergy Skin Testingmentioning
confidence: 99%
“…Based on the age of the individuals evaluated in this study, they were in a development phase. Through physiology constant changes in relation to growth and development take place, depending on genetic factors and extrinsic factors such as physical activity (21,22,23,24,25,26). FEV 1 has increased sensitivity to determine OVD when compared to FEF 25-75% ; the systems for obtaining these parameters are different.…”
Section: Resultsmentioning
confidence: 99%